Detection of Silent Type I Choroidal Neovascular Membrane in Chronic Central Serous Chorioretinopathy Using En Face Swept-Source Optical Coherence Tomography Angiography - Magdy Moussa; Mahmoud Leila; Hagar Khalid; Mohamed Lolah (Journal of Ophthalmology)
Purpose. To evaluate the efficacy of SS-OCTA in the detection of silent CNV secondary to chronic CSCR compared to that of FFA and SS-OCT. Patients and Methods. A retrospective observational case series reviewing the clinical data, FFA, SS-OCT, and SS-OCTA images of patients with chronic CSCR, and comparing the findings. SS-OCTA detects the CNV complex and delineates it from the surrounding pathological features of chronic CSCR by utilizing the blood flow detection algorithm, OCTARA, and the ultrahigh-definition B-scan images of the retinal microstructure generated by swept-source technology. The bivariate correlation procedure was used for the calculation of the correlation matrix of the variables tested. Results. The study included 60 eyes of 40 patients. Mean age was 47.6 years. Mean disease duration was 14.5 months. SS-OCTA detected type 1 CNV in 5 eyes (8.3%). In all 5 eyes, FFA and SS-OCT were inconclusive for CNV. The presence of foveal thinning, opaque material beneath irregular flat PED, and increased choroidal thickness in chronic CSCR constitutes a high-risk profile for progression to CNV development. Conclusion. Silent type 1 CNV is an established complication of chronic CSCR. SS-OCTA is indispensable in excluding CNV especially in high-risk patients and whenever FFA and SS-OCT are inconclusive.